THE ESTIMATED BREEDING VALUE OF SERVICING BULLS OF DOMESTIC BREEDS BY OFFSPRING QUALITY USING THE BLUP METHOD - Yelemesov Kopmagambet Yelemesovich; Baimukanov Aidar Dastanbekovich (Scientific Journal of Pedagogy and Economics, 2020)
The official method for the estimated breeding value of bulls by the quality of offspring in the Republic of Kazakhstan is the Guidelines for examination bulls of dairy and dairy and meat breeds on the quality of the offspring. This method is easily applicable in practice, but it takes a long time to get the results. In particular, it does not take into account genetic differences between groups of animals and the genetic trend in the population. For the assessment of the breeding value of the servicing bulls according to the Guidelines to give an unbiased forecast of the bulls’ genotype, a closed breeding system is necessary, which is impossible under current conditions of the widespread use of imported bulls. The research aimed at improving breeding programs, including assessing the breeding value of servicing bulls of dairy breeds using BLUP methods based on the productive qualities of a dairy cattle array in Kazakhstan, determines the essence of this work. Research in this sphere is driven by the need to harmonize domestic and international methods for evaluating the breeding value of dairy cattle and to introduce the BLUP method in the domestic livestock industry. At this stage, the planned studies are relevant and it will contribute to the improvement of selective and breeding work, taking into account the relationship of dairy productivity with their linear belonging and assessment by the quality of the offspring using the BLUP methods. The work is aimed at identifying the best servicing bulls for subsequent custom mating. At the same time, the possibilities of electronic animal databases are widely used, as well as the possibilities of genomic selection. It is assumed that this selection method will track all genetic variation according to economically valuable traits, which will allow obtaining accurate EBV from candidates for selection. Thus, it can be summarized that the improvement of breeding programs in Kazakhstan using world experience in introducing the latest technologies and programs will make it possible to do breeding of farm animals at an entirely different level. Along with these technologies, the introduction of the genomic evaluation of breeding value in practical breeding will significantly accelerate the rate of genetic improvement of domestic dairy cattle breeds. It was established that the use of the BLUP method in the calculation gives a more accurate selection of animals for mating with the desired traits. Depending on the changing conditions, other factors and effects of influence on the trait can be additionally added to the BLUP AM base model. As of 2013, in all the countries cited, the index of somatic cells in milk has already been taken into account in the structure of the EBV (Estimated Breeding Value) of Holstein animals. At the same time, the structural share of this indicator for countries can be up to 15%. It is noted that for the first time, in 1996, the indicator of the number of somatic cells in milk was included in the calculation of the EBV in countries such as Germany and Israel. It was found that in Israel, the formula for calculating the EBV (PD - Predicated difference) was as follows: , where PD96 – Israelitic EBV 1996 of Holstein cows; КСК – the number of somatic cells in one milliliter of milk. In Germany, the estimation of the breeding value of cows by the number of somatic cells in milk has been carried out since 1996. Before calculating the indices directly, to achieve a normal distribution of the result values of the milk analysis by the number of somatic cells, the data obtained are subjected to a logarithmic transformation. Bulletin the National academy of sciences of the Republic of Kazakhstan 52 In accordance with international standards, the so-called Linear Somatic CellScore (SCS) scale was chosen for the logarithmic transformation of data, the formula: , where, SCS – an estimate of the number of somatic cells; Zellzahl – concentration of somatic cells in 1 ml of milk; log2 – logarithm to base 2. Based on the results of our research, we consider it appropriate to offer for use in Kazakhstan the following formulas for calculating the estimated breeding value by the udder health: , where: Ср – absolute genetic difference of the number for somatic cells of the estimated cow from the average in the population; logСк – logarithm of somatic cell concentration of the evaluated cow; logСп – the average of the logarithms of the concentration of somatic cells in the population; h2 – somatic cell heritability estimate of 0.1. , where: Ис – relative index of the udder health; Сп – the average of the logarithms of the somatic cells concentration in the population; Ср – an absolute genetic difference of the logarithm of the somatic cells concentration of the evaluated cow from the average population value obtained by the formula 15. The statistical model for the estimated breeding value of animals by the exterior is expressed by the following formula. Yijklmnopqr = m + BJi + JSj + Knk + Akl + Abm + Ekan + Betro + BJp+ Tierp + eijklmnopqr, where, Y – trait estimate Y; m – an average of all animals for this trait; BJi – permanent effect of the appraiserclassifier*year of evaluation; JSj – permanent effect of the appraiser-classifier*year of evaluation; Knk – constant effect of maternal calving count; Akl – permanent effect of the duration of the calving interval; Abm – constant effect of the duration of the period between milkings; Ekan – permanent effect of cow age at first calving; Betro – permanent effect of the enterprise or region * herd * year; BJp– random effect of the enterprise * year; Tierp – random effects of individual traits of the animal; eijklmnopqr – error of the impact of random effects of the unaccounted factors. It is appropriate to use as a basis the principles of international methods to evaluate breeds related to domestic breeds. So, as of today, for the assessment of domestic Holstein and black-and-white cattle, it is opportunistically to use the approaches of international methods to assessing Holstein cattle, for fawn-motley breeds - the European methodology for assessing Simmental cattle.